Thymus-derived hormonal and cellular control of cancer - Savino, Wilson; Lepletier, Ailin (Frontiers in Endocrinology, 2023)
The thymus gland is a central lymphoid organ in which developing T cell precursors, known as thymocytes, undergo differentiation into distinct type of mature T cells, ultimately migrating to the periphery where they exert specialized effector functions and orchestrate the immune response against pathogens, tumor cells and self-antigens. The mechanisms supporting intrathymic T cell differentiation are pleiotropically regulated by thymic peptide hormones and cytokines derived from stromal cells in the thymic microenvironment and developing thymocytes. Interestingly, in the same way as T cells, thymic hormones (herein exemplified by thymosin, thymulin and thymopoietin), can circulate to impact immune cells and other cellular components in the immune periphery. Evidence on how thymic function influences tumor cell biology and response of patients with cancer to therapies remains unsatisfactory, although there has been some improvement in the knowledge provided by recent studies. Herein, we summarize research progression in the field of thymus-mediated immunoendocrine control of cancer, providing insights into how manipulation of the thymic microenvironment can influence treatment outcomes, including clinical responses and adverse effects of therapies. We review data obtained from cancer patients and preclinical murine models to evidence the complexity of immunoendocrine interactions underpinning anti-tumor immunity. Keywords: thymus, thymus-derived peptide hormones, T cell subsets, immunoendocrine interactions, cancer therapy.